A team approach to providing refractive error services - Kovin Naidoo; Pirindha Govender (Community Eye Health Journal, 2014)
Worldwide, there are over 640 million people who are vision impaired, simply because they do not have access to a simple eye examination and a pair of spectacles. With 43% of vision impairment being due to uncorrected refractive error, it is no wonder that there have been increased efforts to improve service delivery in this area. However, a recipe for successfully and predictably ‘scaling up’ (expanding) programmes to provide eye examinations and spectacles to everyone in need has thus far remained elusive.